2016
DOI: 10.1007/s13555-016-0118-5
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil in the Treatment of Keloids and Hypertrophic Scars: A Comprehensive Review of the Literature

Abstract: Hypertrophic (HTSs) and keloid scars are common dermatological complaints produced by disruption of the normal wound-healing process. Despite a wide array of therapeutic options available to treat these lesions, HTSs and keloids continue to pose a significant challenge to clinicians in everyday practice. The chemotherapeutic drug 5-fluorouracil (5-FU) is a well-known treatment option reserved for recalcitrant HTSs and keloid lesions. We present clinicians with a comprehensive review of the published data conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 35 publications
(68 reference statements)
0
46
0
1
Order By: Relevance
“…5 A recent review by Shah et al found that 5-FU injection into hypertrophic scars can rarely cause wound dehiscence, scar widening, or tissue necrosis, but it commonly does not have negative side effects. 23 Bleomycin is another injectable medication that can be used to treat hypertrophic scars and keloids. 4 There is little research on bleomycin and scar management.…”
Section: Steroidsmentioning
confidence: 99%
“…5 A recent review by Shah et al found that 5-FU injection into hypertrophic scars can rarely cause wound dehiscence, scar widening, or tissue necrosis, but it commonly does not have negative side effects. 23 Bleomycin is another injectable medication that can be used to treat hypertrophic scars and keloids. 4 There is little research on bleomycin and scar management.…”
Section: Steroidsmentioning
confidence: 99%
“…Keloid scars are an uncommon but troubling complication of dermal injury, with a predilection for younger patients and higher Fitzpatrick skin types, particularly patients of African, Asian, or Hispanic origin with an associated family history [ 1 3 ]. Intralesional corticosteroid injections are considered the first-line treatment for keloids [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Keloid scars are an uncommon but troubling complication of dermal injury, with a predilection for younger patients and higher Fitzpatrick skin types, particularly patients of African, Asian, or Hispanic origin with an associated family history [ 1 3 ]. Intralesional corticosteroid injections are considered the first-line treatment for keloids [ 3 , 4 ]. Corticosteroids can be used alone or in combination with other scar-modulating treatments such as intralesional 5-fluorouracil injection, cryotherapy, surgical excision, radiation therapy, compression therapy, and silicone-based dressings [ 5 – 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Shah et al, 5-FU in conjunction with TAC displayed the highest efficiency in improving the symptoms of scars and decreasing recurrence (30). Our subgroup analysis revealed that TAC in combination with 5-FU was more effective than TAC alone only when TAC was used at a low concentration (10 mg/ml).…”
Section: Discussionmentioning
confidence: 99%